Biology Teaching Methodology at Secondary Schools - Ismoilova Lobar Erkinovna (Zien Journals, 2022)
At the present stage of the socio-economic development of society, fundamental changes have been made to the goals of personal development, which led to the emergence of new categories, methodological approaches and goals in many areas of activity. Secondary education, in particular the professional methodological unit, cannot remain aloof from these trends. With this regard, we analyze and discuss some issues of teaching biology at secondary schools.
Keywords: Biology; healthy lifestyle; methodology; secondary schools